Analisis Laju Pertumbuhan Pajak Hiburan dan Kontribusinya Terhadap Pendapatan Asli Daerah Kabupaten Sukoharjo - Annisa Destein Cindy Qiawati; LMS Kristiyanti; Hadi Samanto (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to “analyze the growth rate and contribution of entertainment tax to Regional Original Income (PAD) in Sukoharjo Regency during the period 2019 to 2024. Entertainment tax is one type of regional tax that has the potential to increase PAD revenue if managed optimally. The method used in this study is quantitative descriptive with a documentation, observation and interview approach using data on the realization of entertainment tax revenue and total PAD from the Sukoharjo Regency Regional Finance Agency. The results of the study show that the growth rate of entertainment tax has fluctuated significantly from year to year, with the highest growth occurring in 2022 at 261.04% after experiencing a drastic decline during the pandemic. Meanwhile, the contribution of entertainment tax to PAD in general is still very low, below 10% each year, with an average contribution of 0.768%. This finding shows that although entertainment tax has shown positive growth in several years, its contribution to PAD is still not optimal. Therefore, a more effective management strategy is needed so that the potential revenue from this sector can be maximized to support regional development.”